Body mass index influences Antimüllerian Hormone and inhibin B in adult males - Zhou, Wen; Zhou, Huanqun (Frontiers in Endocrinology, 2025)
BackgroundThe interplay between obesity and male reproductive health, particularly concerning reproductive hormone fluctuations, is a well-documented concern. Despite varied findings on the BMI-AMH/INHB relationship, this study utilized NHANES data (1999-2004) to clarify this association, aiming to refine the assessment of obesity’s effects on the reproductive hormone levels of adult male Americans.MethodsWe conducted a cross-sectional analysis involving 728 men aged 20 and older. Height and weight were measured by trained staff, and hormone levels were determined using the ELISA method. We performed weighted multiple linear regression to assess the associations between BMI and AMH/INHB, including subgroup interactions, and utilized smoothing curve fitting to analyze nonlinear relationships, along with a threshold effect analysis to evaluate key thresholds.ResultsParticipants in higher BMI quartiles showed a declining trend in AMH levels (P=0.16) and a significant reduction in INHB levels (P<0.01). A negative correlation between BMI and AMH (β: -0.15, 95%CI: -0.23 to -0.06, P<0.01) and INHB levels (β: -2.14, 95%CI: -2.98 to -1.31, P<0.0001) was observed, with these correlations remaining statistically significant (AMH: β: -0.12, 95%CI: -0.23 to -0.01, P<0.05; INHB: β: -1.50, 95%CI: -2.66 to -0.34, P<0.05) after adjusting for relevant confounders. However, the effect size for AMH was relatively low, which may limit its clinical significance. In the fully adjusted model, the increase in BMI in Q4 was linked to decreases of 1.62 ng ml-1 in AMH and 18.20 pg ml-1 in INHB, but these associations were not statistically significant (P>0.05). The association between BMI and AMH/INHB showed no significant interaction effects across all covariates (P>0.05 for the interaction), although negative correlations were present in most subgroups (P<0.05). While both AMH and INHB declined with increasing BMI, they displayed nonlinear relationship at key thresholds of 30.78 kg m-² (below: β=0.02, P>0.05; above: β=-0.30, P<0.05) and 33.86 kg m-² (below: β=-1.24, P=0.05; above: β=-3.22, P<0.05).ConclusionsBMI is associated with a relatively independent negative correlation with serum AMH and INHB levels in adult men, which is more noticeable in obese men and shows no significant interaction with other confounding factors. However, due to the low effect size of BMI/AMH, caution is needed in interpreting its clinical significance. Although we found a non-linear relationship and key thresholds between these variables, further studies with larger sample sizes are needed to confirm these findings.